Renegades - Meyer, Marissa (New York : Feiwel and Friends, an imprint of Macmillan Publishing Group, LLC, 2017)
The Renegades are human, but with extraordinary abilities. They emerged from the ruins of a crumbled society and established peace and order where chaos reigned. As champions of justice, they remain a symbol of hope and courage to everyone... except the villains they once overthrew. Nova has a reason to hate the Renegades, and is on a mission for vengeance. Adrian is a Renegade boy who believes in justice-- and in Nova. But Nova's allegiance is to a villain who has the power to end them both.--
Series information from goodreads.com.
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Friendship -- Juvenile fiction; Loyalty -- Juvenile fiction; Revenge -- Juvenile fiction; Action and adventure fiction; Fantasy fiction; Science fiction